From the Editors - Yunisrina Qismullah Yusuf (Universitas Syiah Kuala, 2014)
This is the front matter of Studies in English Language and Education Volume 1 Number 2 (2014), which includes: • Cover • About the Journal • Editorial Team • Table of Contents